Political economy of pension reforms: Selected general issues and the Polish pension reform case - Marek Góra (IZA Journal of Labor & Development, 2013)
The institutional structures of the various types of European welfare state were established around extra revenues called the demographic dividend that used to be easily available throughout the decades of the 20st century. They, however, ceased to be available at the end of that century. The challenge societies face today is how to manage the institutions having relatively less resources available for their financing. In this paper I analyse selected political economy issues related to pension reforms, such as the worker-retiree conflict of interest, distribution by age of the costs of the loss of demographic dividend, and key goals behind pension reforms. The focus of this paper is on pension reforms in Poland, which actually was an implementation of a thoroughly new pension system. Its design is analysed and discussed from a political economy viewpoint. Furthermore, analysis of the Polish pension system is presented in a broader European context.
Keywords: H55; I31; J11; J18; 330; Rentenreform; Alternde Bevölkerung; Generationengerechtigkeit; Sozialstaat; Polen